Givens
x + y = 3
x =6 - 4y
Solution
Use the top equation to substitute for x in the second equation.
x = 3 - y
Put this result into the second given equation and solve for y
3 - y = 6 - 4y Add 4y to both sides.
3 - y + 4y = 6 Combine on the left
3 + 3y = 6 Subtract 3 from both sides
3 - 3 + 3y = 6 - 3 Combine
3y = 3 Divide by 3
3y/3 = 3/3 Combine
y = 1
=========================
x + y = 3 but y = 1
x + 1 = 3 Subtract 1 from both sides.
x + 1 - 1 =3 - 1
x = 2
Answer
x = 2
y = 1
Answer:
a squared plus b squared = c squared
Step-by-step explanation:
a) 100
b) 153
Honestly I'm just guessing i'm only in algebra 1 and even if i wasn't I suck at geometry
Answer:
60 seconds
Step-by-step explanation:
Hi!
After she goes forward 5 feet (4 seconds), and the backwards 3 feet (another 4 seconds), the total distance forward she travelled is 2 feet. Then, she moved forward 2 feet in 8 seconds.
Then, as this is repeated, she moves forward 2 feet every 8 seconds. After 7 repetitions she travelled 14 feet, and 56 seconds elapsed. Then she goes forward 5 feet in 4 seconds, and she finaly reaches the end of the hallway
(14 +5 > 15)
So, in 60 seconds she reached the end of the hallway.
Answer:
need the answer
Step-by-step explanation:
or want me to work it out
Answer:
exponent
Step-by-step explanation:
In 2^4, 4 is the "exponent."